2008
DOI: 10.1007/s10333-008-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rice straw management and organic fertilizer application on growth and yield of dry direct-seeded rice

Abstract: The objectives of this research were to investigate the effect of rice straw management and application of different types of organic fertilizer on growth and yield of dry direct-seeded rice grown under rainfed conditions. The experiment was conducted in a farmer's field at Muang Yai village, Khon Kaen province in 2005. A split-plot design was used, with the main plot under rice straw management (incorporating into the soil and burning), and sub-plots by type of organic fertilizer (green manure, cattle manure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Prabhakar et al [34] found the highly significant result of neem cake on growth, yield and quality of rose onion (Allium cepa) whereas; Singh et al [35] reported the similar findings on rice crop and Kumpawat [36] on productivity and nutrient uptake of black gram. Similar findings were also reported by the various workers across the country [37][38][39][40].…”
Section: Effect Of Mixed Cake and Fym On Growth And Yield Characterissupporting
confidence: 91%
“…Prabhakar et al [34] found the highly significant result of neem cake on growth, yield and quality of rose onion (Allium cepa) whereas; Singh et al [35] reported the similar findings on rice crop and Kumpawat [36] on productivity and nutrient uptake of black gram. Similar findings were also reported by the various workers across the country [37][38][39][40].…”
Section: Effect Of Mixed Cake and Fym On Growth And Yield Characterissupporting
confidence: 91%
“…However, straw returning does not necessarily increase rice yields [32]. Polthanee et al [46] found that straw returning did not significantly affect rice yield.…”
Section: Effects Of Straw Returning and New Fertilizers Substitution ...mentioning
confidence: 98%
“…Tuyen and Tan (2001) observed that incorporation of rice straw may increase rice yield about 0.4 t ha -1 per season. Polthanee et al (2008) and El-Refaee (2012) reported that incorporation of rice straw into soil did not increase rice yield in the immediate season, however long term effect of straw addition would increase crop yield. Our results supported the finding reported by Man et al (2003) who observed that rice grain yield, in treatment of rice straw after decomposition combined with recommended rate of inorganic fertilizer (NPK), was not significantly different from treatment of 100% recommended rate of inorganic fertilizer application.…”
Section: Grain Yield (T/ha)mentioning
confidence: 99%